Enhancing project manager communication soft skills and risk management practices in Libyan oil and gas construction projects: The role of experience - Elkbuli, Mohamed O.; Nurhidayah, Azmy; Lee, Chia Kuang (Emerald Publishing Limited, 2025)
Purpose: Although there has been an increase in the application of a variety of robust technologies and systems, the oil and gas sector relies on project managers’ soft skills for success because of their vital role. Therefore, this study aims to explore the profound influence of project managers’ soft communication skills on successful risk management within Libya’s oil and gas projects. Design/methodology/approach: A review of relevant literature and a quantitative approach through the administration of a questionnaire were used to determine factors impacting risk management implementation related to managerial communication skills. A total of 246 valid responses were received from the oil and gas companies in Tripoli, Libya. Partial least squares structural equation modelling was used to examine the direct and moderating relationship drawn by the hypotheses. Findings: The findings suggest that managerial soft skills may be used to improve continuous risk management processes and intra-project communication. It was found that the experience is strengthening the positive relationship between written communication soft skills and project risk management implementation among Libyan oil and gas construction projects. Originality/value: This study defines project managers’ soft communication skills and analyzes project managers’ soft communication skills with the role of experience as a moderator. This paper presents a valuable contribution by offering original insights tailored explicitly to the Libyan context. The information presented in this paper is relevant to project managers operating within the oil and gas industry. It also offers a novel approach to risk management in the Libyan oil and gas industry that can improve project efficiency and effectiveness.